2003
DOI: 10.1159/000071464
|View full text |Cite
|
Sign up to set email alerts
|

Self-Biting Induced by Activation of L-Type Calcium Channels in Mice: Dopaminergic Influences

Abstract: The L-type calcium channel activator ±Bay K 8644 induces repetitive self-biting and self-injurious behavior in young mice. Since dopaminergic systems have been implicated in prior studies of these behaviors in both humans and animals, the present experiments were designed to test whether drugs influencing the dopaminergic systems could modify the behavioral responses to ±Bay K 8644. The ability of ±Bay K 8644 to provoke self-biting and self-injurious behavior was increased by amphetamine and GBR 12909, drugs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…A previous study showed that pretreatment of mice with the dopamine-depleting agent tetrabenazine 10 min before BBay K 8644 eliminates self-injurious biting [13]. Pretreatment with 5 mg/kg tetrabenazine was confirmed to reduce self-injurious biting in response to 6 mg/kg BBay K 8644 while simultaneously exaggerating the dystonia (table 3).…”
Section: Pharmacological Modifiersmentioning
confidence: 79%
See 1 more Smart Citation
“…A previous study showed that pretreatment of mice with the dopamine-depleting agent tetrabenazine 10 min before BBay K 8644 eliminates self-injurious biting [13]. Pretreatment with 5 mg/kg tetrabenazine was confirmed to reduce self-injurious biting in response to 6 mg/kg BBay K 8644 while simultaneously exaggerating the dystonia (table 3).…”
Section: Pharmacological Modifiersmentioning
confidence: 79%
“…A single score for each animal was obtained by averaging all scores for the entire recording period. The number of animals with Severe impairment; almost no ambulation, sustained abnormal postures, not upright for majority of time biting sufficient to cause tissue injury was also recorded [13]. If selfinjury occurred, a cotton-tipped applicator was used to prevent further injury so that the experiment could proceed to the planned time point for tissue collection.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the psychostimulant or 6OHDA models, SIB in this model emerges within minutes after the first dose and is accompanied by dystonic motor behavior rather than stereotypical behaviors. Further studies of this model have indicated that striatal dopamine receptors play a role in the expression of SIB in this model and that SIB can be markedly attenuated by nifedipine, an Ltype calcium channel antagonist [Jinnah et al, 1999;Kasim and Jinnah, 2003;Kasim et al, 2006]. SIB is a complex behavior that is likely to involve abnormal function or interaction among multiple cortical and subcortical brain regions.…”
Section: Introductionmentioning
confidence: 93%
“…Five minutes prior to the 8 BayK 8644 injections, half of each 8 BayK 8644 dose group received a subcutaneous injection of 20 mg/kg of 1 of 5 calcium channel antagonists, while the other half received subcutaneous injections of vehicle as controls. The behaviors were assessed as previously described [Kasim et al, , 2006Kasim and Jinnah, 2003]. The animals were observed for 1 min every 10 min for 1 h immediately following 8 BayK 8644 administration, and their behaviors were recorded.…”
Section: Bayk 8644 Modelmentioning
confidence: 99%
See 1 more Smart Citation